Studi Kerukunan Umat Beragama di Desa Lantasan Lama Deli Serdang - Muhammad Ikhsan Harahap; Ahmad Pramudja; Lisa Yuniar; Rizkinta Amelia Batubara; Ahmad Sayuti Malik (PKM-P, 2021)
This article was written as the output of the 144 KKN Group UINSU which includes the study of religious harmony in desa lantasan lama to maintain moderate and tolerant inter-religious harmony. The diversity of ethnic groups, religions and races of the Indonesian people is unique which is the pride of the Indonesian people, but there are not a few conflicts that occur in the diversity itself, therefore creating harmony between people can maintain the integrity and unity of the nation. Maintaining harmony is very important for us so that the religious foundation is solid and strong so that we live to know each other.